2013
DOI: 10.1080/07036337.2013.799938
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Demand for European Union Referendums?

Abstract: Notwithstanding elite opposition to referendums as inconsistent with theories of representative democracy, the 27-nation European Election Study finds that 63 percent of EU citizens want a vote on EU treaties. One explanation is that the majority want more popular participation in politics; another is that referendums are demanded by those negative about the performance of their governors at national and EU levels; a third is that demand is higher where referendums are part of the national context. Multi-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…) had shown that dissatisfaction with institutions of representative democracy is a crucial factor for endorsing direct democracy in many European countries. On the other hand, as Rose and Borz (2013) have proved, national contexts determine the support for referendums, at least on EU-related referendums, and the studies by Donovan et al (2009) and Leininger (2015) point into a samilar direction. The fundamental differences between explanatory factors in different countries insinuate that individual level analysis does not suffice to understand citizens' endorsement for direct democratic decision-making.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…) had shown that dissatisfaction with institutions of representative democracy is a crucial factor for endorsing direct democracy in many European countries. On the other hand, as Rose and Borz (2013) have proved, national contexts determine the support for referendums, at least on EU-related referendums, and the studies by Donovan et al (2009) and Leininger (2015) point into a samilar direction. The fundamental differences between explanatory factors in different countries insinuate that individual level analysis does not suffice to understand citizens' endorsement for direct democratic decision-making.…”
Section: Discussionmentioning
confidence: 98%
“…We also checked for the effect of age since several studies showed that younger people favor direct democracy more strongly than older citizens (Dalton et al 2001;Jeydel & Steel 2002;Donovan & Karp 2006;Rose & Borz 2013;Arnold et al 2014).…”
Section: Control Variablesmentioning
confidence: 99%
“…Instead, we concentrate on the more fundamental question of how referendums interact with the representative democratic system at the system level. 2 With regard to citizens' support for EU-related referendums, research contrasts the cognitive mobilization of political dissatisfaction in the EU (Schuck and de Vreese 2015) with voters' dissatisfaction with the performance of respective governments (Rose and Borza 2013).…”
Section: Motivations Driving the Call For Referendums-intended Effectsmentioning
confidence: 99%
“…With regard to citizens’ support for EU‐related referendums, research contrasts the cognitive mobilization of political dissatisfaction in the EU (Schuck and de Vreese ) with voters’ dissatisfaction with the performance of respective governments (Rose and Borza ).…”
mentioning
confidence: 99%
“…Unfortunately, there are no data on citizens’ perceptions of discrimination in relation to referendums, and we therefore rely on the effective participation of EU citizens in referendums to assess levels of discrimination. Rose and Borz show the percentage of EU citizens who have participated in referendums (either mandatory or optional), compared to the percentage of EU citizens who have not been directly consulted on treaties (Rose and Borz, , p. 622). They show that, in terms of political rights, a large proportion of citizens are discriminated against: on average (for the period 1982–2015) only 8 per cent of Europeans have been given the right to decide on a referendum on Treaty reform.…”
Section: Empirical Evidencementioning
confidence: 99%